Kinetic and thermodynamic studies of silver migration from nanocomposites. (February 2019) - Kim, Min Hee; Kim, Tae-Hyun; Ko, Jung A.; Ko, Seonghyuk; Oh, Jae-Min; Park, Hyun Jin
Abstract: To establish an applicable model and understand the release mechanisms from silver nanoparticle incorporated in polymeric film used in food applications, we investigated silver migration from low-density polyethylene film incorporated with silver nanoparticles in both distilled water and 4 w/v% acetic acid at various temperatures. The silver nanoparticle incorporated film was prepared from silver-containing master batch and was characterized to contain homogeneously distributed nanoparticles. The silver migration from the polymer matrix was well explained by the Korsmeyer-Peppas mathematical model. The resulting n value, ranging from 0.125 to 0.280, indicated that the silver migration followed Fickian diffusion. The kinetic rate constants (k) was higher in 4% acetic acid than in distilled water. According to the Arrhenius equation, the activation energy ( E a ) was calculated to be 31.74 kJ mol −1 for distilled water and 14.19 kJ mol −1 for 4% acetic acid. Hence, the results of this investigation could be useful in predicting the silver release rate and understanding the mechanism of silver release from a LDPE matrix into food simulants. Graphical abstract: Image 1 Highlights: AgNPs were homogenously embedded in LDPE film. Silver migration tests were carried out for ten days. Korsmeyer-Peppas model described silver release from polymer matrix well. Ea for silver release in 4% acetic acid was smaller than distilled water.